Unintended pregnancy and associated risk factors among young pregnant women - Sriprasert I. (Elsevier Ireland Ltd, 2015)
© 2014 International Federation of Gynecology and Obstetrics. All rights reserved. Objective To assess pregnancy intention and the associated risks among young pregnant women. Methods In a descriptive study, pregnant women aged 15-24 years were recruited at a prenatal clinic in Chiang Mai University Hospital, Thailand, between March 1, 2012, and February 28, 2013. Participants were interviewed by trained interviewers using a standardized questionnaire to elicit information about baseline characteristics, pregnancy intention, and contraception practice. Results Overall, 250 participants were recruited (mean age 20.7 ± 2.4 years), and 163 (65.2%) declared that the pregnancy was unintended. The odds of the pregnancy being unintended were increased in students (P = 0.006), women aged 20 years or younger (P = 0.024), and women whose partner was a similar age (P = 0.026). A higher percentage of women with unintended pregnancy than with intended pregnancy reported having no time to use contraception, a perceived difficulty of regular contraceptive use, fear of parents finding out about sexual activity, and embarrassment about using contraception. Conclusion Pregnancy among young pregnant women in Thailand was often unintended. Educational status, age, and age difference between the couple were independently associated with unintended pregnancy.